2017
DOI: 10.5811/westjem.2017.7.34610
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Peripheral Intravenous Line Placement: A Narrative Review of Evidence-based Best Practices

Abstract: Peripheral intravenous line placement is a common procedure in emergency medicine. Ultrasound guidance has been demonstrated to improve success rates, as well as decrease complications and pain. This paper provides a narrative review of the literature focusing on best practices and techniques to improve performance with this procedure. We provide an evidence-based discussion of preparation for the procedure, vein and catheter selection, multiple techniques for placement, and line confirmation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 65 publications
1
64
0
2
Order By: Relevance
“…In this study, for the first time, we demonstrated the feasibility of visualizing clinical needles and a vascular target with real-time PA and US imaging using an LED-based PA system. This paradigm could be useful for guiding peripheral intravenous line placement, particularly in difficult cases that arise from diseases such as diabetes, intravenous drug abuse, and sickle cell disease [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, for the first time, we demonstrated the feasibility of visualizing clinical needles and a vascular target with real-time PA and US imaging using an LED-based PA system. This paradigm could be useful for guiding peripheral intravenous line placement, particularly in difficult cases that arise from diseases such as diabetes, intravenous drug abuse, and sickle cell disease [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…We believe that it is important to separate out PIV placement from other forms of vascular access (e.g., central venous access, arterial access), as the skills involved in peripheral intravenous access differ significantly from other techniques. While central venous and arterial access are performed using a Seldinger technique, peripheral line placement requires advancement of the catheter without the assistance of a guidewire, which may be more challenging for many providers [ 16 ]. As such, we sought to intentionally determine the effectiveness, number of needle passes, and time to placement among this specific group.…”
Section: Reviewmentioning
confidence: 99%
“…This is demonstrated in figures from a number of publications showing typical needle guidance technique in which there is direct contact between the probe and puncture site. [6][7][8] The authors point out that the "CDC guideline does not list venous or arterial catheter placement procedures, or needle biopsies, as examples for semicritical or critical items." 1 This is true; however, guidelines based on Spaulding do not exhaustively list all examples of semicritical or critical items or procedures.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%